Pulmonary Mycoses in Indonesia: Current Situations and Future Challenges - Anna Rozaliyani; Anwar Jusuf; Priyanti ZS; Erlina Burhan; Diah Handayani; Henie Widowati; Satria Pratama; Findra Setianingrum (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Cases of pulmonary mycosis or pulmonary fungal diseases continues to increase in frequency along with the expanding population with impaired immune systems, including patients with pre-existing pulmonary diseases. Changing profile of underlying diseases might cause altering diseases profile as well. In previous decades, Pneumocystis pneumonia was the most common pulmonary mycosis in HIV-infected patients. As the increasing number of TB cases, pulmonary malignancy, chronic obstructive pulmonary disease (COPD) and certain chronic diseases, other pulmonary mycoses also increase such as chronic pulmonary aspergillosis, cryptococcosis, histoplasmosis, and other filamentous fungal infection. Furthermore, the airborne fungal particles of Aspergillus and other fungi could seriously worsen asthma or allergic respiratory diseases. In low- and middle-income countries, including Indonesia, lack of diagnostic facilities may lead to inadequate treatment. It will contribute to poor clinical outcomes with high mortality rates. The awareness among clinicians and other health workers of this epidemiology changes is the important step in early diagnosis and better managemenet of pulmonary mycosis in the future. (J Respir Indo. 2019; 39(3): 210-4)